The Oxford handbook of public management - Ferlie, Ewan, 1956-; Lynn, Laurence E., 1937-; Pollitt, Christopher. (Oxford University Press, 2007)
The public sector continues to play a strategic role across the world and in the last thirty years there have been major shifts in approaches to its management. This text identifies the trends in public management and the effects these have had, as well as providing a broad overview to each topic.